Acquisitions of Contemporary Art in the Czech Republic - Horňáková, Lucia; Patočka, Jiří, 1951-; Drozen, František; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The thesis aims to enrich the theory on the acquisition activity of galleries with knowledge from the Czech Republic and propose a model of an effective acquisition strategy and individual steps leading to successful enhancement of collections, based on the research of established acquisition policies of regional museums. The paper examines the specific steps taken under the State Cultural Policy of the Czech Republic between the years 2015–2020 to help manage the tight financial situation of art museums. In 2017 the Ministry of Culture of the Czech Republic ordained that all new acquisitions of an art institute must be financed from the institute’s investment funds and must not be financed from its operational budgets. The second key point in this cultural policy is the creation of the Acquisition Fund for Contemporary Art. It aims to compensate for the under-financed budgets of museums and galleries established by the regional municipalities, and thus further enhance new acquisitions of contemporary art. While these steps were well-intended, they were not fully embraced by art gallery directors. The low adoption numbers confirm their reservations: only 31 out of 218 art galleries applied for this subsidy during the five years since the Fund was launched. The ambition of the Fund was to disburse 80 mil. CZK (3.2 mil. EUR) annually. To date, however, the Fund has allocated just a fifth. Many mandatory requirements, complicated application procedure, and time-consuming administration of the grant application are the main deterrents to potential applicants. The paper brings a new point of view on the topic of the underfunding of art institutions and their acquisition policies. The research follows the Grounded Theory methodology to enrich the theory of effectiveness of autonomous acquisitions strategies of art museums.
Vedoucí práce: Jiří Patočka
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations